Arterial collaterals and endovascular treatment effect in acute ischemic stroke with large infarct: a secondary analysis of the TENSION tial - Winkelmeier, Laurens Paul; Kniep, Helge; Thomalla, Götz; Bendszus, Martin; Subtil, Fabien; Bonekamp, Susanne; Aamodt, Anne Hege; Fuentes, Blanca; Gizewski, Elke R.; Hill, Michael D.; Krajina, Antonin; Pierot, Laurent; et al. (Radiology, 2025)
Background - Randomized clinical trials have demonstrated that endovascular thrombectomy reduces functional disability in patients with large ischemic stroke; arterial collateral status might be used to select these patients for endovascular thrombectomy. - Purpose - To investigate whether arterial collateral status modifies the treatment effect of endovascular thrombectomy in patients with large ischemic stroke. - - Materials and Methods - The Efficacy and Safety of Thrombectomy in Stroke with Extended Lesion and Extended Time Window (TENSION) trial was a prospective, multicenter, randomized study investigating participants with acute large ischemic stroke due to anterior circulation large-vessel occlusion. Participants with an Alberta Stroke Program Early CT Score of 3-5 were enrolled at 41 participating centers between July 2018 and February 2023. Participants were randomly assigned to undergo either endovascular thrombectomy with best medical treatment or best medical treatment alone within 12 hours from stroke onset. Collateral status was graded on pretreatment single-phase CT angiography (CTA) images using the Tan score and dichotomized into poor (grade, 0-1) or good (grade, 2-3) based on the extent of collateral supply filling the affected middle cerebral artery territory. The primary outcome was the shift on the 90-day modified Rankin Scale (mRS). - Results - Of 253 randomized patients, 201 with pretreatment CTA were included (median age, 74 years; IQR, 66-80 years; 103 [51.2%] female patients; 103 [51.2%] patients underwent endovascular thrombectomy). Endovascular thrombectomy compared with best medical treatment (adjusted common odds ratio [OR], 3.69; 95% CI: 2.12, 6.54; P < .001) and good collaterals compared with poor collaterals (adjusted common OR, 2.88; 95% CI: 1.63, 5.11; P < .001) were independently associated with a shift in the 90-day mRS scores toward better functional outcomes. The treatment effect of endovascular thrombectomy over best medical treatment was not modified by collateral status (interaction, P = .88). The treatment effect of endovascular thrombectomy versus best medical treatment was found in patients with good collaterals (adjusted common OR, 3.93; 95% CI: 1.65, 9.69; P = .002) and poor collaterals (adjusted common OR, 3.92; 95% CI: 1.86, 8.52; P < .001). - Conclusion - In this secondary analysis of data from the TENSION trial, endovascular thrombectomy reduced 90-day functional disability compared with best medical treatment in patients with good and poor collaterals. These findings suggest that patients with large ischemic stroke manifesting within 12 hours after onset should undergo endovascular thrombectomy irrespective of single-phase CTA collateral status. - ClinicalTrials.gov Identifier: NCT03094715 - © RSNA, 2025 - Supplemental material is available for this article. - - See also the editorial by Benomar and Raymond in this issue.